Visual Outcomes of Ultrathin-Descemet Stripping Endothelial Keratoplasty versus Descemet Stripping Endothelial Keratoplasty - Droutsas, Konstantinos (J Ophthalmol, 2018)
PURPOSE: To examine the impact of graft thickness (GT) on postoperative visual acuity and endothelial cell density after ultrathin-Descemet stripping automated endothelial keratoplasty (UT-DSAEK) versus conventional DSAEK. METHODS: The medical records of all patients who underwent DSAEK at our institute during a 2-year period were reviewed. After excluding subjects with low visual potential, 34 eyes were divided into two groups based on the postoperative GT as measured with anterior segment optical coherence tomography (AS-OCT): an UT-DSAEK group (GT ≤ 100 μm, n=13 eyes) and a DSAEK group (GT > 100 μm, n=21 eyes). The groups were compared with regard to best-corrected visual acuity (BCVA), subjective refraction, central corneal thickness (CCT), GT, and endothelial cell density (ECD). RESULTS: Preoperative BCVA (logMAR) was 1.035 ± 0.514 and 0.772 ± 0.428 for UT-DSAEK and DSAEK, respectively (P=0.072). At 6 months postoperatively, BCVA was 0.088 ± 0.150 following UT-DSAEK and 0.285 ± 0.158 following DSAEK (P=0.001). CONCLUSION: DSAEK grafts with a thickness under 100 μm offered better visual outcomes during the early postoperative period.